2022
DOI: 10.1177/18369391221099370
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the home learning environment: Introducing the home learning ecosystem

Abstract: This commentary paper offers a broader definition of the construct of the home learning environment and an updated conceptual framework. Recent empirical research has burgeoned on the home learning environment and is mainly examining how processes mediate the way parenting practices influence a child’s development and learning. By introducing the Home Learning Ecosystem, the paper presents a holistic view of the different home learning environment components and focuses on the interaction among those. It also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Their interactions during these activities were characterized as warm and supportive, with low levels of conflict and inconsistent discipline. Overall, the findings of this study confirmed that the families' engagement in HLAs and the quality of HLIs are fundamental elements of a modern HLE (Gregoriadis and Evangelou, 2022).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Their interactions during these activities were characterized as warm and supportive, with low levels of conflict and inconsistent discipline. Overall, the findings of this study confirmed that the families' engagement in HLAs and the quality of HLIs are fundamental elements of a modern HLE (Gregoriadis and Evangelou, 2022).…”
Section: Discussionsupporting
confidence: 75%
“…A strength of the present study is that it attempted to assess three distinct types of parent-child interactions during their shared HLAs. Therefore, this study suggests that an essential feature of the HLE is not only what parents do with children (Sylva et al, 2004) but also how they do it (Dearing and Tang, 2010;Gregoriadis and Evangelou, 2022); thus, emphasis in intervention programs can be placed in supporting the quality of interactions during learning activities.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations